2017
DOI: 10.1177/0363546517713198
|View full text |Cite
|
Sign up to set email alerts
|

Differences of RNA Expression in the Tendon According to Anatomic Outcomes in Rotator Cuff Repair

Abstract: The downregulation of inflammatory response genes and the upregulation of cell differentiation genes in torn rotator cuffs at the time of surgery are related to rotator cuff healing. These results provide useful baseline information for future biological studies on rotator cuff healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Of the studies, 2 were deemed poor quality, 79,81 15 were moderate quality, 2,4,13,27,37,39,47,49,55,56,59,64,69,70,82 and 9 were high quality. 3,7,11,12,16,38,42,47,55,70,72,80,82 These results are outlined in Table II. A further breakdown of these scores is shown in Supplementary Tables S7-S9.…”
Section: Quality Assessmentmentioning
confidence: 76%
See 2 more Smart Citations
“…Of the studies, 2 were deemed poor quality, 79,81 15 were moderate quality, 2,4,13,27,37,39,47,49,55,56,59,64,69,70,82 and 9 were high quality. 3,7,11,12,16,38,42,47,55,70,72,80,82 These results are outlined in Table II. A further breakdown of these scores is shown in Supplementary Tables S7-S9.…”
Section: Quality Assessmentmentioning
confidence: 76%
“…7,12,37,47,59,69,79,81 13 investigated the association of altered gene expression in human shoulder tissue with RCTs, 2,4,11,13,16,39,42,49,55,56,64,70,82 and 5 investigated genetic associations with healing after surgical repair of RCTs at !1 year following surgery. 3,27,38,72,80 Study characteristics are described in Supplementary Tables S4-S6.…”
Section: Individual Study Characteristics and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found 15 SNPs of the TNC gene and they were significantly associated with degenerative lesions. 30 Ahn et al 31 evaluated 14 patients who underwent repair and concluded that negative regulation of inflammatory response genes and positive regulation of cell differentiation genes at the time of surgery are related to rotator cuff healing.…”
Section: Rotator Cuff Injurymentioning
confidence: 99%
“…Ahn et al 31 avaliaram 14 pacientes que foram submetidos ao reparo e concluíram que a regulação negativa de genes de resposta inflamatória e a regulação positiva de genes de diferenciação celular no momento da cirurgia estão relacionados à cicatrização do manguito rotador.…”
Section: Lesão Do Manguito Rotadorunclassified